Il Museo di Storia Naturale dell'Università degli Studi di Firenze. Le collezioni mineralogiche e litologiche | The Museum of Natural History of the University of Florence.The Mineralogical and Lithological Collections - Giovanni Pratesi (Cataloghi e collezioni, 2012)
The Museum of Natural History of the University of Florence, founded in 1775 by Grand Duke Pietro Leopoldo d'Asburgo Lorena, is one of the oldest and most prestigious scientific museums in the world. The fourth volume on the Collections of the Mineralogy and Lithology Section, published like the previous volumes by the Firenze University Press, fits perfectly in the series dedicated to the collections of the University's Museum System. The first part of the book describes in great detail the paths that led to the formation of the collections, starting with those dating to the Medici period and arriving at the specimens collected during recent expeditions. The second part illustrates and documents the extraordinary specimens of minerals, hardstone carvings and meteorites which represent the material patrimony of this section. Particular attention is given to the holotypes, the Elban Collection and the minerals of pegmatites, as well as the methods and solutions adopted to realize the project of the new museum exhibition set-up. The third and last part describes the studies carried out on the materials: from the minerals of the systematic collections to the rock specimens that recount not only the geodiversity of a region but also the history of a city.